Characteristics and outcome of patients with relapsed/refractory Hodgkin lymphoma following front-line escalated BEACOPP-based chemotherapy: a report from the Australasian Lymphoma Alliance. Issue 14 (5th December 2020) - Harwood, Matthew; Hodges, Georgina; Tan, Xuan; Cheah, Chan Y.; Lim, Kenneth; Ku, Matthew; Tam, Constantine; Lagerlof, Ingemar; Cochrane, Tara
Abstract: The optimal management of the small number of patients who experience early failure of eBEACOPP in Hodgkin lymphoma (HL) is unclear. We identified 12 patients with HL who progressed within 12 months of the front-line therapy between January 2010 and July 2019. Median time of first progression following diagnosis was 7 months (range 2.1–13.2). Nine patients proceeded to stem cell therapy following salvage therapy (8 autografts, 1 allograft). Seven patients received novel therapy after relapse, of these, 6 were alive at census, versus 2 out of 5 of those who had standard therapy alone. At the end of follow up (median 22 months), 4 were deceased from progressive disease, 6 were in complete remission and 2 in partial remission on continuing therapy. The outcome of patients with primary refractory HL to eBEACOPP therapy is better than expected and the use of a novel agents after relapse may be a contributing factor.